Modelling the strengthening factors for competitive position of apparel retailing in India - Singh A.K.; Samuel C. (My University, 2025)
Purpose: The aim of this paper is, first, the desire to present the issue of retail sector competitiveness with the simultaneous determination of factors having an impact on competitiveness and their development. The main aim is to identify the factors and relationships among those factors to strengthen the competitive positioning of apparel retail stores. Design/methodology/approach: The literature review and experts’ opinion helped to identify the key factors. The relationships among the factors were obtained by using interpretive structural modelling (ISM). Experts’ opinions were collected again for the fuzzy direct relationship matrix. Factors were further classified by driver and dependence power using the fuzzy matrix of cross-impact multiplications applied to classification (FMICMAC) analysis. Findings: Total nine strengthening factors (SFs) identified here, and developed an integrated model using ISM and classified it into four clusters with the help of driver and dependence power. The model hierarchy shows the interrelationships among these SFs. The retail environment, Information and Communication Technology, technology adoption and human resource management were found to be the most significant factors needing some spotlight by the top-level authority. Research limitations/implications: The study will help managers to understand the variables and their relationships and to select the right factors to achieve a potential competitive position. Relationships among the factors were obtained through the opinions of experts and academicians. Expert opinion is a subjective judgement, and biasing in judgement might affect the result. Originality/value: The research presents the first kind of an integrated model using ISM and FMICMAC to identify nine factors and classify them by their driving and dependence power. The developed model helps in the identification, classification and selection of factors as per requirement. This study will assist managers to understand the variables and their relationships and to select right factors to achieve a potential competitive position. © 2018, Emerald Publishing Limited.